Evaluation of the incisive papilla as a guide to the maxillary central incisors and canine teeth position in Iraqi and Yemenian samples - Khalaf, Hanan A. (Journal of the Faculty of Medicine Baghdad, 2009)
Back ground: This study was conducted to estimate the relation ship of the incisive papilla to the antero posterior arrangement of the maxillary anterior teeth in a two different groups (Iraqi and Yemenian groups), because incisive papilla is considered as a reliable and relatively stable anatomic land mark.Materials and Methods: Maxillary and mandibular stone casts were collected from 100 dental students, (50) of Iraqi dental students in Baghdad university and (50) of Yemenian dental students in Ibb university at the 3rd and 4th classes. Age ranged from 21-25 years. Alginate impression, dental stone, stock trays were used. Photographic technique was used to measure anatomic land marks located on dental casts. A computerized digital caliper (CDC) tool was used in the measurements which were made on scanned images of dental casts .The distances from midpoint and posterior point of incisive papilla were measured .The area on the incisive papilla where the inter canine distance passed was noted , paired t- test and chi-square test were used to analyze the data.Result: the data obtained suggested that the distance from the labial surface of maxillary central incisors was ranged from 8.9 to 9.92 mm from the midpoint of incisive papilla, this measurement was 8.9 mm in Iraqi sample and 9.92 mm in Yemenian sample. Also the distance from the from the labial surface of maxillary central incisors was ranged from 11.33 to 12.34 mm from the posterior border of incisive papilla , this measurement was 11.33 mm in Iraqi sample and 12.34 mm in Yemenian sample The mean distance of the inter canine line joining the canine cusp tips was 31.9 mm in Iraqi sample and 35.66 mm in Yemenian sample. The differences between Iraqi and Yemenian scores (distance from the labial surface of maxillary central incisors to the mid point and posterior border of incisive papilla in addition to the scores of inter canine distance) were statistically significant (p